Accidents rate of the Polish State Fire Service officers during service in the years 2015-2022 - Łukasz Dudziński; Łukasz Czyżewski; Tomasz Kubiak; Tomasz Milczarczyk (Nofer Institute of Occupational Medicine, 2023)
Background The profession of a firefighter is fraught with a significant risk of injuries. Firefighters operate in hazardous zones to mitigate threats and combat fires. Aim of work is to evaluate the accident rate of the officers of the Polish State Fire Service in connection with their service, considering direct participation in rescue operations, and other official duties between the years 2015-2022. Material and Methods An 8-year analysis was conducted from reports covered the number of accidents, the number of injured firefighters, the age of the officers, the circumstances of the event, and the type and location of the injury. This includes fire and rescue operations, exercises, training, official trips, sports activities, and technical work related to equipment. Results Between 2015 and 2022, there were 12 588 individual and group accidents in various circumstances. Most firefighter accidents occurred during rescue and firefighting operations, as well as during sports activities which dominate as the cause of injuries among firefighters in the observed period (37.8%), and injuries related to rescue and fire-fighting activities constitute 28.5%. Other work activities of firefighters cause 33.7% of injuries. In 2020 was a clear reduction in the number of accidents per 1000 employed firefighters in each observed parameter (total, interventions, sport) while maintaining the average level of firefighter employment (M±SD 30 099±224). Conclusions The most frequent circumstances of injury are slippery and challenging spaces, surfaces, and carelessness. The most common type of body injury is a dislocation and sprain concerning the ankle joint, foot. The most frequent causes of work-related injuries for firefighters, as the results indicate, are participation in team sports and fire-fighting and rescue operations. The most commonly occurring medical consequences resulting from a firefighter's injury are fractures, sprains, and contusions of various body areas. Firefighters are most burdened with injuries in the age group 26-35 years old. Med Pr Work Health Saf. 2023;74(6):469-77.